Propriedades estruturais e vibracionais dos dipeptídeos L-alanil-L-fenilalanina e L,L-dileucina - Silva, Cristiano Balbino da (2019)
In the present study the hydrophobic dipeptides L-alanyl-L-phenylalanine (C12H16N2O3) and L,L-dileucine hydrate (C12H24N2O3·0.87H2O) were studied using Raman and infrared spectroscopy techniques, together with computational models, based on Functional Density Theory (DFT), with the purpose of investigating the structural and vibrational properties of these materials. First-principles calculations using the Functional Density Theory were carried out on an isolated molecule in the zwitterionic form, and the Polarizable Continuum Model was used to simulate solvent effects. The structures were initially obtained from a crystallographic file, optimized for the molecular conformation of lower energy, and then subjected to the frequency calculation to obtain the normal modes of vibration, where we made use of the Gaussian09 package together with the B3LYP functional and the 6-31 G(d,p)++ basis sets. The assignments for each normal mode of vibration were made with the aid of molecular visualization software and the VEDA4 program (which provides the potential energy distribution for each mode). The Raman and infrared spectroscopy experiments were made, at ambient conditions in the region of 40 to 3500 cm−1 and 130 to 4000 cm−1, respectively. For the L,L-dileucine dipeptide, were performed DSC thermal analysis experiments (from room temperature up to 473 K (~200 °C)), Raman spectroscopy experiments with pressure variation up to 8.2 GPa, X-ray synchrotron with pressure up to 26.2 GPa, and experiments of X-ray diffraction at low temperatures down to 103 K (~ -170 °C), and at high temperatures up to 473 K (~200 °C), in order to understand the behavior of the dipeptide L,L-dileucine hydrate under the variation of these thermodynamic parameters. The experiments under high pressures, both Raman and X-ray diffraction with synchrotron radiation, showed significant changes, suggesting a phase transition between 2.3 and 2.9 GPa. The results of X-ray diffraction at low temperatures present subtle changes indicating a possible conformational change in the range of 223 to 233 K (~-50 to -40 °C), while at high temperatures drastic changes occur between 373 and 403 K (~100 and 130 °C), indicating the occurrence of phase transition in this temperature range. Some explanations for these modifications are also furnished.